Effects of packaging materials and ventilation placement on strawberry shelf-life - Alani, Maadh F; Embaby, Mohamed G; Joshi, Prabesh; Pahariya, Prachi; Choudhary, Ruplal (Food, Agriculture and Natural Resources - NETWORKS, 2025)
The strawberry is a popular fruit known for its color and flavor, but it is highly perishable due to its high respiration rate with rapid ripening and lack of natural protective covering. Existing packaging techniques for strawberries primarily focus on marketing purposes that often do not provide sufficient protection against mechanical and physiological damage. In this study, different packaging techniques were investigated, considering the cushioning and respiration needs of strawberries. The material and design of the packaging were optimized to enhance strawberry storage and preservation. The effects of packaging material on strawberry weight loss and shelf life were investigated. Two types of packaging were investigated at 4°C with a relative humidity ranging from 74% to 84% using two packaging materials in the form of egg-crate made of molded pulp or Styrofoam, which was compared to common clamshell packages made of polyethylene material. Different strawberry attributes were measured including firmness, color, mold, weight, taste and aroma. Results showed that Styrofoam egg-crate packages had the least weight loss compared to molded pulp and control packages. The ventilation design had a significant effect within treatment but not between treatments. Sensory test results showed that Styrofoam packages had better attributes in terms of firmness, color, aroma, and overall acceptability compared to molded pulp. The packaging type had a significant effect on strawberry shelf life, while the ventilation location did not. The findings suggest that packaging materials play an important role in prolonging strawberry shelf life.